THE IMPORTANCE OF USING ARCHIVE FUNDS DOCUMENTS IN RESEARCH WORKS - Kholmamat KHIDIROV (Scholar Express Journal, 2023)
This article talks about the importance of using documents from archival funds in research, the organizational methods of the educational process in the field of archival studies at the faculty of history, independent work of students in the educational process, and the nature and characteristics of archival specialist training, as well as methodological work in the field of archival studies. is conducted
Keywords: Research; archive; fund; document